Chronic Heart Failure with Preserved Ejection Fraction in A Comorbid Patient: Issues in Verification of A «Difficult» Diagnosis - O. V. Ponomareva; E. A. Smirnova; K. A. Shukis (Архивъ внутренней медицины)
Chronic heart failure with preserved ejection fraction (HFpEF) is a complex, heterogeneous, multi-organ systemic syndrome characterized by significant morbidity and mortality. Currently, it has acquired the character of an epidemic of the 21st century. The clinical observation describes a typical story of an elderly patient suffering from coronary artery disease (CAD), dyslipidemia, atherosclerosis of the brachiocephalic arteries against the background of arterial hypertension (AH), obesity, type 2 diabetes mellitus (DM), complicated by diabetic retinopathy, polyneuropathy, nephropathy with development of chronic kidney disease (CKD) and HFpEF. The condition was aggravated by the presence of chronic pyelonephritis of a single kidney (right nephrectomy for renal abscess in 2013), bronchial asthma. The limitations of modern scales for determining the pre-test probability of HFpEF and low natriuretic peptide levels are demonstrated. Comorbidity, poorly controlled hypertension, diabetes, low adherence to therapy led to the development of acute vascular accident, then, repeated cerebrovascular accident — to a fatal outcome. Histologically, perivascular and interstitial sclerosis in the myocardium and epicardium was detected, which is the basis of diastolic dysfunction in HFpEF.A clinical example reflects the difficulties of verification of HFpEF-diagnosis, as well as the mutual pathogenetic influence of concomitant pathology, which can lead to an unfavorable outcome if recommendations are not followed.